Ionic liquid modified electroactive polymer-based microenvironments for tissue engineering - Hermenegildo, B. (2022)
The combination of electroactive polymers and ionic liquids (ILs) has been gaining much attention for tissue engineering. Thus, this work reports on the development of oriented electrospun fibers and films based on poly(vinylidene fluoride) (PVDF) and polyhydroxybutyrate-co-hydroxyvalerate (PHBV) blended with the IL choline acetate ([Chol][Ac]). The inclusion of IL into the polymer matrix induces a decrease in the fiber orientation, particularly for PHBV + IL electrospun fibers. The effect of IL on the thermal properties of both electrospun fibers and films is more noticeable when it was incorporated in PHBV, resulting in a general decrease of the melting temperature. For both polymer matrixes, an increase in the surface roughness of the films is observed as well as a decrease of the thermal stability and surface wettability upon IL incorporation, regardless of IL content. Upon inclusion of the IL, the samples presented ionic conductivity values of 3.46 × 108 S cm1 for PHBV + IL 15% electrospun fibers, 1.53 × 1010 S cm1 for PVDF + IL 15% fibers, and 3.27 × 1010 S cm1 for PVDF + IL 15% films. Finally, the potential of the materials for tissue engineering is demonstrated by cytocompatibility assays.